2011
DOI: 10.1107/s0108270111014521
|View full text |Cite
|
Sign up to set email alerts
|

Two isomorphous transition metal complexes containing a protonated diaminopurine ligand: diaquabis(2,6-diamino-7H-purin-1-ium-κN9)bis(homophthalato-κO)nickel(II) tetrahydrate and the cobalt(II) analogue

Abstract: The two isomorphous title compounds, [M(C(5)H(7)N(6))(2)(C(9)H(6)O(4))(2)(H(2)O)(2)]·4H(2)O or M(2+)(Hdap(+))(2)(hpt(2-))(2)(H(2)O)(2)·4H(2)O {where dap is 2,6-diaminopurine, H(2)hpt is homophthalic acid [2-(2-carboxyphenyl)acetic acid] and M is Ni(II) or Co(II)}, consist of neutral M(2+)(Hdap(+))(2)(hpt(2-))(2)(H(2)O)(2) monomers, where the M(II) cation lies on an inversion centre and its MN(2)O(4) octahedral environment is defined by one N atom (from Hdap(+)), two O atoms (from one hpt(2-) dianion and one wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…A point of interest in these systems is the possibility of introducing extra ligands as bridges and thus obtaining grid structures and/or clusters, which are appealing not only structurally but also for their potential application in ion-exchange, catalysis, molecular absorption, optical, electronic and magnetic areas (Ma et al, 2000;Wang et al, 2002;Xu et al, 2002;Benelli & Gatteschi, 2002;Pan et al, 2004). In parallel, our investigation of carboxylate complexes has showed that the incorporation of some purine derivatives, like 2,6-diaminopurine (dap), might facilitate crystallization, either through their inclusion as neutral cocrystallization agents (Atria et al, 2009) or as counter-ions (Atria, Morel et al, 2011), or even as coordinating ligands (Atria, Corsini et al, 2011;. In parallel, our investigation of carboxylate complexes has showed that the incorporation of some purine derivatives, like 2,6-diaminopurine (dap), might facilitate crystallization, either through their inclusion as neutral cocrystallization agents (Atria et al, 2009) or as counter-ions (Atria, Morel et al, 2011), or even as coordinating ligands (Atria, Corsini et al, 2011;.…”
Section: Commentmentioning
confidence: 99%
“…A point of interest in these systems is the possibility of introducing extra ligands as bridges and thus obtaining grid structures and/or clusters, which are appealing not only structurally but also for their potential application in ion-exchange, catalysis, molecular absorption, optical, electronic and magnetic areas (Ma et al, 2000;Wang et al, 2002;Xu et al, 2002;Benelli & Gatteschi, 2002;Pan et al, 2004). In parallel, our investigation of carboxylate complexes has showed that the incorporation of some purine derivatives, like 2,6-diaminopurine (dap), might facilitate crystallization, either through their inclusion as neutral cocrystallization agents (Atria et al, 2009) or as counter-ions (Atria, Morel et al, 2011), or even as coordinating ligands (Atria, Corsini et al, 2011;. In parallel, our investigation of carboxylate complexes has showed that the incorporation of some purine derivatives, like 2,6-diaminopurine (dap), might facilitate crystallization, either through their inclusion as neutral cocrystallization agents (Atria et al, 2009) or as counter-ions (Atria, Morel et al, 2011), or even as coordinating ligands (Atria, Corsini et al, 2011;.…”
Section: Commentmentioning
confidence: 99%
“…The tautomers H 2 (N1,N3)dap + , H 2 (N3,N9)dap + and H 2 (N7,N9)dap + do not have received crystallographic support. The H 2 (N1,N7)dap + tautomer acts as N9-donor ligand in two isomorphous compounds having all-trans octahedral complex molecules [M II (H 2 dap) 2 (hpt) 2 (H 2 O) 2 ]·4H 2 O (M = Co or Ni, htp = homophthalato(2-) ligand) [56] (see Scheme 1). The κN9-H 2 (N1,N7)dap+ coordinating role was consistent not only with the highest proton affinity of the donor atom but also to its less steric hindrance.…”
Section: Cp#mentioning
confidence: 99%
“…[References: OQUMOD and OQUMUJ (Atria, Corsini et al, 2011); AWICUF ; QUDKAC, QUDKEG, QUDKIK, QUDKOQ, QUDKUW and QUDLAD (Yang et al, 2009); WULXEG (Badura & Vahrenkamp, 2002). ]…”
Section: Metal-organic Compoundsmentioning
confidence: 99%